STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI-NILAI KARAKTER PADA SISWA - Saputra, Deli (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2021)
This study aims to describe 1) the strategy of Islamic Religious Education (PAI) teachers in instilling student character in SMPN 1 Bandar Lampung and 2) Implementation of Islamic Religious Education (PAI) teachers in instilling student character in SMPN 1 Bandar Lampung. This research is a qualitative research by taking the location in SMPN 1 Bandar Lampung. The data collection technique uses observation, interviews, and documentation and then the data is analyzed by means of reduction steps, data presentation, and drawing conclusions. The results of this study are 1). The strategy of PAI teachers in instilling the character of students at SMPN 1 Bandar Lampung, namely through habituation and example, while the character strategies instilled in students are characters between religious, disciplined, caring for the environment, responsibility, tolerance and independence, namely by getting used to students and motivate and exemplify from the teacher himself. 2). The implementation of the strategy of Islamic Religious Education (PAI) teachers in order to instill the character of students at SMPN 1 Bandar Lampung is one of them getting used to saying greetings, praying Zuhur in congregation, and experiencing obstacles both from the students themselves and the school environment.